AN ANALYSIS OF A TEACHER WRITING LESSON PLAN - Nandasari, Horiyeh; Sofian, Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to analyse an English teacher writing the lesson plan for teaching the students of grade X of SMKN 2 Sungai Raya academic year 2018/2019. In this research the researcher analysed an English teacher in writing the lesson plan. The actions were designed to know how the teacher made the lesson plan for teaching. The subject of this researcher was an English teacher who taught in grade X of SMKN 2 Sungai Raya academic year 2018/2019. The method of this research was a descriptive study. The researcher analysed the teacher by giving questionnaire and doing an interview. From the questionnaire and the interview the data were collected by the researcher, the researcher analysed and described it in this research. The result of this research showed that the teacher was good enough in understanding the way to be a good teacher, but unfortunately the teacher did not make the lesson plan by himself, it became a problem for the teacher to have good teaching in the process of teaching learning. By this result, the researcher of this research can conclude that the English teacher of grade X in SMKN 2 Sungai Raya did not have good quality in writing the lesson plan.Keywords: Analysis on a Teacher, Lesson Plan, Descriptive Study.Â